2003
DOI: 10.1177/1045389x03014002005
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Behavior of MR Fluids in Squeeze, Torsional and Valve Modes

Abstract: In order to understand the effectiveness of MR fluids in some applications, such as bearings, this work focuses on the properties of MR fluids under squeeze mode, torsional mode and squeeze combined with torsional mode. A special device was designed and fabricated to perform these experiments, which were carried out on an Instron Multiaxial Testing Machine. The hysteresis loops of the MR fluids were studied for different intensities of electric current, frequency, strain amplitude and angle amplitude. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Kulkarni et al [16] have obtained similar results from the dynamic loadings of a hydrocarbon-based MR fluid under squeeze mode. They found less effect of the tensile stresses under various applied currents as compared to the compressive stresses.…”
Section: Combinations Of Compressive and Tensile Stressesmentioning
confidence: 68%
“…Kulkarni et al [16] have obtained similar results from the dynamic loadings of a hydrocarbon-based MR fluid under squeeze mode. They found less effect of the tensile stresses under various applied currents as compared to the compressive stresses.…”
Section: Combinations Of Compressive and Tensile Stressesmentioning
confidence: 68%
“…The compressive and tensile behaviors of MRP that we have discussed above reflect the quasistatic mechanical performance. The dynamic mechanical behavior is another important aspect to assess the performance of MRP for academia as well as for some potential applications [Farjoud et al (2009); Farjoud et al (2011); Kulkarni et al (2003)]. Oscillatory shear mode is the mostly used dynamic characterization method to investigate the rheological properties of MR fluids [de Vicente et al (2011b)], while the oscillatory squeeze behaviors of MR fluids are paid less attention though it is also valuable to understand the MR mechanism.…”
Section: Oscillatory Squeeze Behaviors Of Mrpmentioning
confidence: 99%
“…In addition, there seems no report about the investigation on the oscillatory squeeze behavior of MR fluids. Some preliminary applications by using MR fluids working under squeeze mode in damper [Ahn et al (2004); Carmignani et al (2006); Kulkarni et al (2003); Wang et al (2005)] and mount [Farjoud et al (2011)] have been tried; superior performance was presented in these squeeze-film dampers than that of the devices working under shear mode.…”
Section: Introductionmentioning
confidence: 99%
“…This squeezestrengthening phenomenon, also known as the superstrong effect (Tao, 2001), could drastically increase the torque-to-weight ratio of MRF devices, but has not yet been used in practical applications due to limited understanding and predictability of the phenomenon. Moreover, its feasibility in rotary (shear-type) devices is questionable, as it has been demonstrated that superimposing squeeze motion to a shearing flow does not always result in an increase in MRF yield stress (Kulkarni et al, 2003). To our knowledge, the only recorded design attempt of a super-strong device is an MRF brake, which uses a double magnetic circuit to compress the MRF during shear motion (Sarkar and Hirani, 2013).…”
Section: Introductionmentioning
confidence: 99%